(untitled) (diségno, 2022)
Now in its third edition, the After the Damages Advanced Training Summer School project on risk management and the impacts on the existing built heritage resulting from natural or man-made disasters consolidates both the didactic results and the interest and participation of national and international part- ners in the Academy’s activities. The areas of investigation and com- parison, also on an international scale, have concerned, among other things, the effects of climate change on the conservation of cultural heritage. This has been done starting from an interdisciplinary and integrated approach to the issues related to emergency management, safety, and reconstruction following catastrophic events of a different nature. [read more]